Phalloplasty by radial forearm free flap in the context of female-to-male gender reassignment surgery - Hu, W; Henry, A S; Rouanet, M; Pop, A; Claudic, Y; Vais, B; Perrier, A; Tehri, I; Saraoui, W; Perruisseau-Carrier, A (Annales de chirurgie plastique et esthétique, 2023)
The aims of this article are to provide an overview of the technique of phalloplasty by radial forearm free flap in the context of female-to-male gender reassignment surgery, with a specific focus on surgical technical details and the prevention of postoperative complications.AIMSThe aims of this article are to provide an overview of the technique of phalloplasty by radial forearm free flap in the context of female-to-male gender reassignment surgery, with a specific focus on surgical technical details and the prevention of postoperative complications.In the light of our 30 years of experience in caring for female-to-male transgender individuals and conducting a critical review of the literature, we exhaustively present our technique of radial forearm free flap phalloplasty in female-to-male gender reassignment surgery.METHODSIn the light of our 30 years of experience in caring for female-to-male transgender individuals and conducting a critical review of the literature, we exhaustively present our technique of radial forearm free flap phalloplasty in female-to-male gender reassignment surgery.The technique of radial forearm free flap phalloplasty, utilizing a one-stage approach for neourethral and neophallus construction based on the "tube within a tube" principle, not only achieves an aesthetically pleasing appearance of the neophallus resembling a normal penis with tactile and erogenous sensitivities but also yields a functional neourethra and satisfactory penile rigidity using implants for standing voiding and sexual intercourse. This intricate surgical procedure demands not only meticulous execution of all surgical maneuvers but also high-level postoperative care. Despite refinements in technique over recent decades, aesthetic sequelae at the donor site of the flap remain subject to criticism, and postoperative complications, particularly of vascular and urological nature, remain significant.RESULTSThe technique of radial forearm free flap phalloplasty, utilizing a one-stage approach for neourethral and neophallus construction based on the "tube within a tube" principle, not only achieves an aesthetically pleasing appearance of the neophallus resembling a normal penis with tactile and erogenous sensitivities but also yields a functional neourethra and satisfactory penile rigidity using implants for standing voiding and sexual intercourse. This intricate surgical procedure demands not only meticulous execution of all surgical maneuvers but also high-level postoperative care. Despite refinements in technique over recent decades, aesthetic sequelae at the donor site of the flap remain subject to criticism, and postoperative complications, particularly of vascular and urological nature, remain significant.Future optimization of the surgical technique for this procedure will be imperative to minimize postoperative complications and establish a true technical "gold standard" for phalloplasty in female-to-male transgender individuals.CONCLUSIONFuture optimization of the surgical technique for this procedure will be imperative to minimize postoperative complications and establish a true technical "gold standard" for phalloplasty in female-to-male transgender individuals.